Efektifitas Belajar dan Menghafal melalui Media Lagu dengan Aplikasi SUNO AI pada Pelajaran Desain Grafis - Heriyanto Heriyanto; Amelia Makmur (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Cognitive abilities in terms of memorizing each student who is different in addition to the low interest in reading students need innovative, creative and effective steps to support learning activities and processes. This study aims to analyze how effective the effect of using song media with the help of the SUNO AI application on the memorization ability of students in learning graphic design material in class 12 Visual Communication Design at Atisa Dipamkara Vocational High School.The research design chosen was descriptive quantitative with a quasi-experiment design. The data collection technique chosen at the initial stage was to distribute questionnaires to students to get an initial picture of students in general. Furthermore, to see the difference in cognitive abilities between the experimental class and the control class, a pre-test before intervention and post-test after intervention were conducted. Prior to hypothesis analysis, prerequisite tests were conducted including Normality test with Liliefors test to ensure that the data were normally distributed, and Homogeneity test with Bartlett test to ensure that the data came from a population with homogeneous variance. The results of the Paired-Samples T-Test in the Experimental Class showed that the P-value was smaller than the alpha value (0.05), so H0 was rejected and H1 was accepted. This confirms that the use of song media with the help of SUNO AI is effective in improving the learning and memorization ability of students at the Vocational High School level.